Neogyptis vostokensis Pleijel & Rouse & Sundkvist & Nygren 2012, SP. NOV. - Pleijel, Fredrik; Rouse, Greg W.; Sundkvist, Tobias; Nygren, Arne (Zenodo, 2012)
NEOGYPTIS VOSTOKENSIS SP. NOV. (FIG. 13) Type material: Holotype (SIO-BIC A2498), c. 75 paratypes SIO-BIC A2499 – A2504). Type locality: Sea of Japan, Peter the Great Bay, Vostok Bay, Vostok Marine Biological Station, 42°53.7′N, 132°44.0′E, 0.5–1 m, amongst lumps of Modiolus modiolus (Linnaeus, 1758). Etymology: Named for Vostok Bay, the type locality. Material examined: Russia, Sea of Japan, Peter the Great Bay, Vostok Bay, Vostok Marine Biological Station. Holotype (SIO-BIC A2498, fixed in formaldehyde), 42°53.7′N, 132°44.0′E, 0.5–1 m, amongst lumps of M. modiolus , colls FP and Radashevsky 11.v.1994; 17 paratypes (SIO-BIC A2499, fixed in formaldehyde), same collecting data as holotype; eight spms (FP collection, fixed in formaldehyde; mounted on SEM stubs for SEM), same collecting data as holotype; c. 25 paratypes (SIO-BIC A2500, fixed in formaldehyde), 42°53′N, 132°44′E, 6–8 m, amongst lumps of M. modiolus and mud with H 2 S, SCUBA, coll. Belokonev 13.v.1994; nine paratypes (SIO-BIC A2501, fixed in formaldehyde), 42°53′N, 132°44′E, 3–5 m, amongst Crassostrea gigas (Thunberg, 1793), SCUBA, coll Belokonev 15.v.1994; ten paratypes (SIO-BIC A2502, fixed in formaldehyde), 42°53.7′N, 132°44.0′E, 0.5– 1 m, amongst Mytilus sp. growing on buoy, colls FP and Radashevsky 17.v.1994; three paratypes (SIO- BIC A2503, fixed in formaldehyde), 42°53.5′N, 132°44.1′E, 3 m, sand, SCUBA, coll. Radashevsky 19.v.1994; c. 25 paratypes (SIO-BIC A2504, fixed in formaldehyde), Point Pashennikov, 42°53.0′N, 132°43.9′E, 6–8 m, coarse gravel with some detritus, SCUBA, coll. Radashevsky 20.v.1994. Description: Length up to 4.5 mm for 27 segments. Live animals transparent yellowish white, eyes black; preserved yellowish white. Body outline in dorsal view of equal width with tapering posterior end (Fig. 13A). Prostomium rounded rectangular, slightly wider than long (Fig. 13B). Palpophores cylindrical, palpostyles cylindrical to elongated ovoid with rounded tips; palpophores and palpostyles of equal length. Paired antennae about as long as ...